Behaviouristic in The Novel The Call of The Wild - Pordan, Melfi; Maca, Sudirman; Abeng, Andi Tenri (Humaniora: Journal of Linguistics, Literature, and Education, 2023)
This study aimed to discover the types of behavior of The Call of The Wild characters and also what impacts of human behaviour that can affect towards animals in the The Call of The Wild Novel. In this research the descriptive qualitative method are applied through the theory of B. F Skinner. The results of the study showed that there were two types of behavioristic model found the novel The Call of The Wild, namely operant conditioning and classical conditioning so that positive and negative reinforcement processes are formed in The Call of The Wild novel. Besides that, there were each character with a different personality that influences the dog’s behavior that resulting in the impact on the dogs behaviours it was that the dog (Buck as a dog) experienced changes in behavior when faced with different owners or characters and these changes occurred depending on the surrounding environment, therefore the presence of humans behaving badly, kindly, assertively, violently and the treatment received by human that leading to attack, showing aggressive behaviour due to fear or discomfort, exhausted resulting in showing a drastically losing body weight, laziness and disobedient as a negative impact and showing obedient, happy and protective nature as a positive impact